Implementation of SAW Method for Determining SCRM Model as Business Strategy in Higher Education - Rusliyawati Rusliyawati; Damayanti Damayanti; Febrizal Nata Prawira (Proceeding International Conference on Information Technology and Business, 2020)
The rapid growth of Internet and social media led to new developments in the field of social customer relationship management (SCRM). An organization was required to determine the direction of business strategies by utilizing the technology in various activities so that the large-scale business was identified through the speed, accuracy, and efficiency of the information development. The quality of good business strategies was achieved by providing social media-based facilities in the form of various predetermined assessment indicators that were able to make a good contribution for companies. The objective of this study was developing the website-based application for analyzing and calculating the characteristics of each of SCRM models as a business strategy through the Simple Additive Weighting (SAW) approach. The system developed in this study was extreme programming system development and black box testing. The independent variables of this study were Facebook, Instagram, Twitter, and YouTube. Moreover, the dependent variable of this study was the SAW method. The result of this study showed that YouTube social media was the recommended social media used as a business strategy for higher education by 0.888Keyword : Social Customer Relationship Management, Simple Additive Weighting, Business Strategy